Dissimilarity of Turbulent Transport of Momentum and Heat Under Unstable Conditions Linked to Convective Circulations. Issue 8 (12th April 2023) - Zhang, Lu; Zhang, Hongsheng; Zhang, Xiaoye; Li, Qianhui; Wu, Bingui; Cai, Xuhui; Song, Yu; Zhu, Tong
Abstract: The dissimilarity between the turbulent transport of momentum and heat under unstable conditions and its physical mechanisms are investigated in this study, based on the multiple‐level turbulence observation from the Tianjin 255‐m meteorological tower. The transport dissimilarity is observed from the surface layer to the lower part of mixed layer as atmospheric instability increases. Although the transport dissimilarity is accompanied by the development of plumes and thermals under unstable conditions, plumes and thermals can produce intense transport both of momentum and heat simultaneously. It is convective circulations induced by vigorous thermals that cause transport dissimilarity. The horizontal divergence generated by convective circulations imposes a dominant large‐scale reduction in the along‐wind velocity component near the surface, which is related to increased counter gradient transport of momentum, while the temporal variations in temperature mainly reflect the role of plumes and thermals and thus the transport of heat is predominantly down‐gradient. This difference in respective physical processes subsequently leads to dissimilar transport between momentum and heat under unstable conditions. Therefore, it is of great interest to represent the influence of convective circulations on the momentum‐flux estimation in future investigations, aiming to improve the boundary‐layer parameterization schemes for mesoscale numerical weather models. Plain Language Summary: The turbulent transport of momentum and scalars (e.g., heat, water vapor, carbon dioxide) between the land surface and the atmosphere is crucial for the prediction of weather and climate. It has been considered that turbulence transports momentum and scalars similarly in atmospheric numerical models. However, an increasing number of studies have shown that there is often the dissimilarity between the turbulent transport of momentum and scalars in the actual atmosphere. Specially, the transport dissimilarity between the momentum and heat is more significant with increasing atmospheric instability, and it coincides with the appearance of plumes and thermals (i.e., a kind of turbulent coherent structures). Until now, how the coherent structures physically cause the transport dissimilarity is still debated. Using the multiple‐level turbulence observation from the Tianjin 255‐m meteorological tower, it is clarified that it is not the presence of plumes and thermals that directly causes the transport dissimilarity, but other physical processes relevant to them, which is proved to be convective circulations in this study. The horizontal divergence generated by convective circulations affects the wind field in the surface layer, and then modifies the transport of momentum, leading to the dissimilar transport between momentum and heat under unstable conditions. Key Points: Transport dissimilarity between momentum and heat exists from the surface layer to the lower part of mixed layer under unstable conditions Plumes and thermals induce intense transport both of momentum and heat Transport dissimilarity links to the horizontal divergence caused by convective circulations as the atmospheric instability increases